Lines of succession : heraldry of the royal families of Europe - Maclagan, Michael; Louda, Jirí (London : Orbis, 1981)
Introduction to heraldry - Medieval England - Great Britain - Scotland - Denmark - Norway - Sweden - Netherlands and Luxemburg - Belgium - Medieval Spain - Hapsburg and Bourbon Spain - Liechenstein - Monaco - Dynastic relations - Medieval and modern France - Napoleon - Burgundy - Hapsburg and modern Austria - Bohemia - Hungary - Brandenburg, Prussia and Germany - Bavaria and the Palantine - Brunswick and Hanover - Saxony - Württemberg and Baden - Brabant, Thuringia, Hesse and Lorraine - Mecklenburg and Oldenburg - Holy Roman Empire - Portugal - Savoy, Sardinia and Italy - The Two Sicilies - Tuscany, Modena, Milan, Mantua and Parma - Poland - Russia - Greece - Yugoslavia, Serbia, Montenegro, Rumania and Bulgaria
Keywords: Kungahus -- Europa; Royal houses -- Europe